2020
DOI: 10.17583/mcs.2020.4827
|View full text |Cite
|
Sign up to set email alerts
|

“Yo lo que Quiero es Trabajar”. Hombres que Trabajan en el Sector del Cuidado Social

Abstract: In this article we explore the experiences and perceptions of men in social care occupations in Spain in order to understand their reasons for going into care work, their continuation in the sector, how they are perceived, and to what extent gender matters in their work experiences. We use data from the ongoing qualitative research we are undertaking in Catalonia (Spain) on men as carers; this text is based on 31 semi-structured interviews with male workers in the social care sector. Our results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
1
Order By: Relevance
“…In India, even if they enter female-dominated occupations, the majority of men try to make sure that they conform to the mainstream / traditional masculine values. This is in contrast to the study undertaken by Bodoque-Puerta et al (2019) in Spain which found that the male social caregivers "distance themselves from the values of traditional masculinity to construct an alternative masculinity" (p.220). It was observed that the male care providers consider knowledge to perform physiotherapy as something that would give them an upper hand compared to their female counterparts.…”
Section: Strategies Employed To Sustain In the Fieldcontrasting
confidence: 75%
“…In India, even if they enter female-dominated occupations, the majority of men try to make sure that they conform to the mainstream / traditional masculine values. This is in contrast to the study undertaken by Bodoque-Puerta et al (2019) in Spain which found that the male social caregivers "distance themselves from the values of traditional masculinity to construct an alternative masculinity" (p.220). It was observed that the male care providers consider knowledge to perform physiotherapy as something that would give them an upper hand compared to their female counterparts.…”
Section: Strategies Employed To Sustain In the Fieldcontrasting
confidence: 75%